Serum, but Not Saliva, CXCL13 Levels Associate With Infiltrating CXCL13+ Cells in the Minor Salivary Gland Lesions and Other Histologic Parameters in Patients With Sjögren’s Syndrome - Chatzis, Loukas; Goules, Andreas V.; Stergiou, Ioanna E.; Voulgarelis, Michael; Tzioufas, Athanasios G.; Kapsogeorgou, Efstathia K. (Frontiers in Immunology, 2021)
Recent studies suggest that elevated CXCL13 serum levels in patients with primary Sjögren’s syndrome (pSS) associate with minor salivary gland (MSG) histologic features, disease severity, as well as high-risk status for non-Hodgkin lymphoma (NHL) development and NHL itself. In contrast, limited discriminative value of CXCL13 saliva levels has been reported. Prompt by these reports, we sought to validate the clinical utility of CXCL13 by investigating potential correlations of serum and saliva levels with MSG histopathologic [including CXCL13+-cell number, severity of infiltrates and germinal center (GC) formation], serologic and clinical parameters, as well as NHL. CXCL13 levels were evaluated in paired serum and saliva specimens of 45 pSS patients (15 with NHL; pSS-associated NHL: SSL), 11 sicca-controls (sicca-complaining individuals with negative MSG biopsy and negative autoantibody profile), 10 healthy individuals (healthy-controls) and 6 non-SS-NHLs. CXCL13+-cells were measured in paired MSG-tissues of 22 of pSS patients studied (including 7 SSLs) and all sicca-controls. CXCL13 serum levels were significantly increased in pSS and SSL patients compared to sicca- and healthy-controls and were positively correlated with the CXCL13+-cell number and biopsy focus-score. Serum CXCL13 was significantly higher in pSS patients with GCs, rheumatoid factor, hypocomplementemia, high disease activity, NHL and in high-risk patients for NHL development. CXCL13 saliva levels were significantly increased in SSL patients (compared to non-SS-NHLs), patients with GCs and in high-risk for NHL patients. Univariate analysis revealed that CXCL13 serum, but not saliva, levels were associated with lymphoma, an association that did not survive multivariate analysis. Conclusively, our findings confirm that serum, but not saliva, levels of CXCL13 are associated with histologic, serologic and clinical features indicative of more severe pSS.